The protective effect of cannabinoid type II receptor agonist AM1241 on ConA-induced liver injury in mice via mitogen-activated protein kinase signalling pathway. (11th August 2021) - Wu, Yafeng; Ma, Run; Long, Cuizhen; Shu, Yuanhui; He, Ping; Zhou, Yan; Xiang, Yining; Wang, Yuping
Introduction: The endocannabinoid system plays an important role in regulating the immune responses in inflammation. At present, there are no good clinical drugs for many immune liver diseases. Methods: We explored the protective effect of the cannabinoid type II (CB2) receptor agonist AM1241 on the liver of mice with acute liver injury caused by concanavalin from the perspective of inflammation and immunity. Pathological evaluation in hepatic tissue was examined by haematoxylin and eosin (HE) staining and the levels of biochemical parameters in the serum were measured by automatic biochemical analysis. The content of inflammatory factors was measured by enzyme-linked immunosorbent assay and real-time quantitative reverse transcription polymerase chain reaction (real-time PCR). The liver apoptosis-related proteins were observed by immunohistochemistry. The expression of liver injury-related proteins was analysed by Western blot. Immune cells were isolated from the liver of mice and studied in vitro. Results: Reduced levels of alanine transaminase and aspartate transaminase were observed in ConA-induced liver injury mice treated with AM1241, together with attenuated liver damage evidenced by H&E staining. Moreover, AM1241 inhibited the protein and gene expression levels of TNF-α, IL-6 and IFN-γ in the livers of mice. The phosphorylation levels of p38, JNK, ERK1/2, P65 and cAMP response element-binding protein (CREB) in the mouse were significantly reduced in AM1241 pretreatment, while the level of p-JNK increased. In addition, the P/T-P65 and P/T-CREB of the AM1241 pretreatment group were significantly reduced. The results of immunohistochemistry measurement are consistent with those of Western blotting. The CB2-mediated effect is through macrophage-like Kupffer cells. Conclusion: Our study suggests that the ConA-induced liver injury model in mice is protected by CB2 agonist AM1241 by modulation of CB2 receptor-rich immune cells, for example, Kupffer cells. Reduced inflammatory responses regulate apoptosis/cell death in the liver particularly hepatocytes and other parenchymal cells.